XÁC ĐỊNH TÍNH ĂN MÒN KHÍ QUYỂN TẠI CÁC TRẠM THỬ NGHIỆM KHÍ HẬU CỦA TRUNG TÂM NHIỆT ĐỚI VIỆT - NGA - V.A., Karpov; V.N., Ivonhin; Chử, Minh Tiến; O.L., Mikhailova; Iu.L., Covaltruc; N.L., Philitrev; Nguyễn, Quang Tân (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
DETERMININGTHE ATMOSPHERIC CORROSIVENESS IN CLIMATIC TESTING STATIONS OF RUSSIAN - VIETNAMESE TROPICAL CENTERThis paper presents the the methods to determine the atmospheric corrosiveness by new ISO 9223-2012 standard using the meteorological-environmental parameters or corrosion rate of standard metal samples in 1 year. The meteorological- environmental data of the climatic testing stations of Russian - Vietnamese tropical center and their corrosivenessare are given. In addition the corrosion rate of metal samples in these stations is determined. The meteorological-environmental data and corrosion rate of standard metal samples can predict the lifetime and capacity of metallic details and techniques made of the experimental metalls.